2018
DOI: 10.1007/s11604-018-0756-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation versus cryoablation for T1b renal cell carcinoma: a multi-center study

Abstract: Other than primary technique efficacy, the clinical outcomes between RFA and cryoablation were similar in patients with cT1b RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 35 publications
1
57
0
Order By: Relevance
“…The present study is the third to evaluate functional outcome (D À 4.4 ml/min/1.73m 2 ) after cryoablation for T1b RCC. Hasegawa et al evaluated 23 patients treated by cryoablation for T1b RCC and found a mean eGFR loss of 7.6 ml/min/ 1.73m 2 at 1 month after treatment [4]. Gunn et al [10] evaluated 37 patients treated by cryoablation for T1b RCC and found no significant change in renal function after cryoablation (p > .05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study is the third to evaluate functional outcome (D À 4.4 ml/min/1.73m 2 ) after cryoablation for T1b RCC. Hasegawa et al evaluated 23 patients treated by cryoablation for T1b RCC and found a mean eGFR loss of 7.6 ml/min/ 1.73m 2 at 1 month after treatment [4]. Gunn et al [10] evaluated 37 patients treated by cryoablation for T1b RCC and found no significant change in renal function after cryoablation (p > .05).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a higher local recurrence rate, intermediate metastasis-free and cancer-specific survival rates are comparable between the two approaches. RF carries a high risk of repeat ablation for tumors larger than 3 cm [4,5]. Cryoablation is a useful option for large tumors because of the ability to visualize the ablation zone during the procedure, and possibility of complementary treatment [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well‐known thermal ablation techniques include radiofrequency ablation, cryoablation and microwave ablation . Previous research comparing radiofrequency ablation with cryoablation for renal tumors showed no significant differences in treatment effects and side‐effects . However, the most recent of those reports stated that when efficacy of the technique was defined as coverage of the tumor by the ablative zone, the primary efficacy rate of the technique was significantly higher in the cryoablation group than in the radiofrequency ablation group …”
Section: Introductionmentioning
confidence: 99%
“…As its efficacy is comparable to nephrectomy, renal cryoablation has become an accepted treatment for small renal tumors as an alternative to surgery, especially in patients who are poor candidates for surgery and patients with multiple renal tumors or a single kidney . In Japan the number of patients undergoing percutaneous cryoablation has been increasing, particularly since its appearance on the list of approved procedures by the Japanese national health insurance program in 2011 …”
Section: Introductionmentioning
confidence: 99%